Legal right to housing in India - Mukherjee, Anindita
This book on constructing a legal right to housing in India seeks to achieve three ends: first, examine the costs incurred in translating a moral right into the language of the law; second, unpack the ways in which existing law and policy impact the realisation of the right to housing and situate any attempt to legally guarantee the right within this context; and finally, begin thinking through the many complexities that will arise should the right be articulated within the law. A comprehensive chronology of central housing law and policy provides the descriptive background for this analytical text, while also acting as a rich introductory resource on the subject. Asserting a need as a right and then seeking legislative recognition for the right is a formula often used in rights struggles. This book takes a critical look at this process, in order to facilitate informed engagement with the law.
Includes bibliographical references and index.
Keywords: Right to housing; Housing; Housing policy